IoT health monitoring system for preventing and controlling risk in confined space using microcontrollers - A. Saeed, H.; H. Mazlan, M.; H. Ibrahim, A.; E. Hamzah, H.; H. Qasim, H.; A. Gore, A.; I. Hamza, M. (International Journal of Engineering and Technology, 2019)
Healthcare monitoring is a field that caught many researchers from the computer science community in the last decade. In the literature, various levels of people have been considered when proposing a health monitoring system. However, some aspects are still not adequately tackled such as monitoring workersâ€™ health status within confined space where workers would be located in underground environment with less oxygen and a lot of dust. This paper proposes an IoT health monitor system for worker in confined places. The proposed system utilizes four types of microcontroller sensors including LM35 for measuring body temperature, heart beat rate sensor, blood pressure sensor and LPG gas sensor. All the aforementioned sensors are being connected via a GPS module in order to transmit the readings into a smartphone application. A simulation has been conducted to test the proposed sensors where competitive commercial measures have been used as a benchmark. Result of simulation showed that the sensors have fair accuracy that is near-identical to the benchmark.Â